Identifying Ecotourism Potentials Using DEMATEL-GIS Hybrid Approach. A Case Study of Mashhad Urban Area, Iran - ALIZADEH-ZOERAM, Ali; AGHAJANI, Hossein (Journal of Environmental Management and Tourism; Vol 10 No 2 (2019): JEMT VOlume X Issue 2(34) Spring 2019, 2019)
The aim of this study was to identify the potentials of ecotourism in the Mashhad urban area using DEMATEL- GIS hybrid approach. To this end, sixteen criteria in the form of four dimensions (topography, natural, environmental and socioeconomic) were considered. Finally, ecotourism potentials were presented in maps at three levels of criteria, dimensions and final status based on the fuzzy membership functions defined. The findings of this research provide a framework for identifying various potentials of ecotourism within the research area and for implementing the plans and measures necessary for its proper development .